KERANGKA PENGEMBANGAN SITUS CANDI LOSARI: Kajian Awal untuk Pengembangan Penelitian, Pendidikan, dan Kepariwisataan - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2008)
Archaeological research in Losari Temple site also implicates how the site should be developed. There are three frameworks: research framework, educational framework, and tourism framework. Research framework is related to Losari Temple and how its information or its data may support archaeological research or other disciplines. A framework for education is related to how the information may support educational program. In the framework for tourism there are four most important aspects: how to preserve the site, how to present the information, how to manage the access and accomodation, and how to promote the object.